Nonradioactive in situ hybridization for detection of mRNAs encoding for peroxisomal proteins: heterogeneous hepatic lobular distribution after treatment with a single dose of bezafibrate. - Schad, Arno; Fahimi, H. Dariush; Völkl, Alfred; Baumgart-Vogt, Eveline (Journal of histochemistry & cytochemistry, 1996)
We present a nonradioactive in siru hybridization (ISH) protocol for detection of mRNAs in rat liver encoding for three peroxisomal proteins: catalase and urate oxidase as representatives of high-level abundance mRNAs and trifunctional protein (PH) as that of low-level abundance mRNAs. In addition to normal rats, animals treated for 24 hr with a single dose of bezafibrate were studied. The use of perfusion-fixation with 4% depolymerized paraformaldehyde/0.05% glutaraldehyde combined with paraffin embedding and the application of digoxigenin-labeled cRNA probes provided optimal cytological resolution and high sensitivity comparable to that of radioactive ISH. In parallel experiments, the same digoxigenin-labeled cRNA probes were used for Northern and semiquantitative dot-blot analysis of isolated RNAs. In control animals, the mRNAs for catalase and urate oxidase were uniformly distributed across the liver lobule and were confined to liver parenchymal cells. The bile duct epithelial and the sinusoidal cells remained negative. The specificity and the high resolution of our protocol were further substantiated by reciprocal localization of transcripts for albumin and glyceraldehyde-3-phosphate dehydrogenase in different regions of the liver lobule and for catalase in the proximal tubules of the renal cortex. Whereas in control livers the transcripts for PH were barely detectable, a strong signal was found in pericentral hepatocytes of bezafibratetreated animals, corresponding to an 8-10-fold increase of mRNA detected in dot-blots. In contrast, the urate oxidase mRNA was reduced by more than 50%, with diminution of staining in pericentral regions of the liver lobule. The mRNA encoding for catalase was only slightly affected. Further applications of this protocol should be helpful in elucidation of the cell-specific transcriptional regulation of peroxisomal proteins in various organs under normal and pathological conditions.